Decision Support System To Help Buyers Determine The Quality Of Used Car Purchases With The Web-Based Simple Additive Weighting (SAW) Method - Vina Oktaviani; ZE Ferdi Fauzan Putra (JOINCS (Journal of Informatics, Network, and Computer Science), 2019)
This research aims to design and build a decision support system for the selection of used cars that can help Indonesian people in choosing used cars as they wish. This system was built using the Simple Additive Weighting (SAW) method to calculate values ​​derived from used car criteria that will produce the best used car ranking in accordance with consumer desires. Accurate calculation results can be obtained because the Simple Additive Weighting (SAW) method not only calculates the closest distance to the positive ideal solution, but also calculates the farthest distance with the negative ideal solution to determine the chosen alternative. This research resulted in a system that is able to display the best used car recommendations according to the criteria parameters filled by the user according to the desires / needs of the system. These results can be used to assist users in choosing a used car in accordance with their wishes without having to go to a used car showroom